SMARCA4/BRG1-Deficient Non-Small Cell Lung Carcinomas: A Case Series and Review of the Literature - Nambirajan, Aruna; Singh, Varsha; Bhardwaj, Nishu; Mittal, Saurabh; Kumar, Sunil; Jain, Deepali (Archives of pathology & laboratory medicine (1976), 2021)
Somatic mutations in SMARCA4 (SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily A, member 4) gene and/or BRG1 (Brahma-related gene 1) loss identifies a subset of non-small cell lung carcinomas (NSCLCs) lacking alterations in EGFR (epidermal growth factor receptor), ALK (anaplastic lymphoma kinase), and ROS1 (ROS proto-oncogene 1) genes. Preliminary observations suggest responsiveness to immunotherapy and targeted therapies. To study BRG1 loss in NSCLCs and elucidate the clinicopathologic profile of such SMARCA4-deficient NSCLCs. Non-small cell lung carcinomas diagnosed during 6 years were subject to immunohistochemistry for BRG1 and BRM (Brahma). Tumors with BRG1 loss were stained with antibodies against thyroid transcription factor 1 (TTF-1), p40, cytokeratins, hepatocyte paraffin 1 (Hep Par 1), Sal-like protein 4 (SALL4), CD34, SRY-box 2 (SOX2), chromogranin, synaptophysin, p53, integrase interactor 1, ALK, and ROS1. EGFR mutation testing was performed by polymerase chain reaction-based method. Among 100 NSCLCs tested, 4 cases (4%) showed BRG1 loss. The histology ranged from solid adenocarcinomas (n = 1) to large cell/poorly differentiated carcinomas (n = 3) with clear cell cytology in 2 cases. All showed loss/reduction of BRM with variable cytokeratin and SALL4 expression, and were negative for TTF-1, p40, Hep Par 1, ALK, ROS1, and EGFR mutations. CD34 and SOX2 were negative in all 4 cases. Isolated BRM loss was common (21%), distributed across all NSCLC subtypes including squamous cell carcinomas and a hepatoid adenocarcinoma. BRG1 loss occurs in a subset of TTF-1/p40-negative poorly differentiated NSCLCs. Identification and follow-up will clarify the prognosis, diagnostic criteria, and potential for therapeutic personalization.